Домик на Юге: рассказы / Маша Трауб - Трауб Маша (АСТ, 2009)
Экземпляры: ф.4 (20181205) / Инвентарный номер: 718 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Т 65 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44